A study on the factors that influence motivation among employees at Corporate Office Kulim (M) Berhad / Nur Shahferah Roslan - Roslan, Nur Shahferah (Faculty of Business and Management, 2014)
Employee is an important asset in the organization. The success and failure of the organization depends on the employee performance. This paper aims to study on the factors that influence motivation among employee at Corporate Office Kulim (M) Berhad. The independent variables that involved in this study are rewards, working environment and managerial trustworthiness. For this project paper, this research focused on the employees been worked at Corporate Office Kulim (M) Berhad, Ulu Tiram, Johor. 100 questionnaires were distributed to employees. The questionnaires were used to obtain and collected the data from the respondent. Simple random sampling has been used in this study as a sampling technique. The researcher used SPSS program version 20.0 where the researcher has used reliability analysis, frequency analysis, descriptive analysis, correlation analysis and regression analysis. In the end of this paper, the researcher has provided several recommendations regarding the factors that can influence employee’s motivation.